Health, Complexity and non-communicable Diseases - Alfredo Darío Espinosa Brito (Revista Finlay, 2023)
Science and the production of scientific knowledge are changing, the parts are not the objective, it is the whole and its interrelationships. Health faces new challenges that cannot be explained by reductionist conceptions. The attempt to group various conditions in non-communicable diseases that cause three quarters of deaths in the world and in Cuba is recognized as one of the great challenges of sustainable development. Many of them, despite their heterogeneity and multi-causality, share common risk -and protective- factors, which can be reversed with integrated actions. The frequent comorbidity of these diseases with other entities, polymorbidity, and the role of aging in their appearance are discussed. The presence of the chronic inflammatory state of the endothelium and the dysfunction of this organ are highlighted as a possible final common path of the pathogenesis, evolution and subsequent clinical expression of many of the so-called non-communicable diseases, true systemic syndromes. A group of recommendations are given to improve its prevention and control, with emphasis on the community participation of all, where the social sciences can contribute a lot to achieve better results, without forgetting individual or group susceptibility to suffering certain non-communicable diseases. It is considered that managers, health professionals, formal and informal leaders, people, groups and communities must be trained and updated in concepts and approaches to these diseases to achieve their purposes.